1997
DOI: 10.1177/096914139700400309
|View full text |Cite
|
Sign up to set email alerts
|

Breast Screening: Adverse Psychological Consequences One Month after Placing Women on Early Recall Because of a Diagnostic Uncertainty. A Multicentre Study

Abstract: Background-It was the original intention of the UK National Health Service Breast Screening Programme (NHSBSP) to place women who were not diagnosed with cancer on three yearly routine recall (RR). In 1994-5 approximately 16500 women, aged 50 to 64, were placed on early recall (ER) at a shorter time interval, of which about 98% will have a normal result. This large number exceeds the expectations of the NHSBSP. Objective-To establish the adverse psychological consequences (PCs) for women one month after placem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 32 publications
4
81
1
Order By: Relevance
“…Four of the studies were prospective cohorts, 59,[101][102][103][104][105][106] one of these studies 107 included a nested interview study but this was only published as a conference poster, four were retrospective cohorts, 55,61,108,109 two had a cross-sectional design, [110][111][112][113] one of these studies 114 produced national guidelines that contained research findings and one was a RCT 115 of an intervention to improve reattendance.…”
Section: Primary Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the studies were prospective cohorts, 59,[101][102][103][104][105][106] one of these studies 107 included a nested interview study but this was only published as a conference poster, four were retrospective cohorts, 55,61,108,109 two had a cross-sectional design, [110][111][112][113] one of these studies 114 produced national guidelines that contained research findings and one was a RCT 115 of an intervention to improve reattendance.…”
Section: Primary Researchmentioning
confidence: 99%
“…The papers follow the same cohort of women over this time but the methods used appear to vary at different time points and it is not always clear on what basis the women included in the study have been selected or how the main outcome measure, the PCQ, has been used. The study includes women with normal mammograms as the control group and compares them with women with false-positive outcomes according to the process used in Orton 1991 n = 1592 109 Ong 1998 guidelines 114 Ong 1997(b) n = 1493 110 Austoker 1994 n = 1493 112 Ong 1996 n = 84 111 Brain 2008 n = 1321 102 Ellman 1989 n = 752 105 Bull 1991 n = 750 106 Ong 1997(a) n = 877 104 Brett 1998 n = 284 103 Brett 2001 n = 505 59 Clements 2008 n = 58 107 Tyndel 2007 n = 2250 101 Smith 1991 n = 103 104 (n = 877), reported primarily on the adverse psychological consequences of being placed on early recall (6 or 12 months recall rather than 3 years) at T1. These effects were measured using the PCQ negative scale which has 12 items on a four-point Likert scale (scored 0-3).…”
Section: Psychological Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…This 12-item scale is a valid and reliable tool that was developed specifically for breast cancer screening settings [11][12][13] . A 5-point response scale, ranging from 0 ("not at all") to 4 ("quite a lot of the time"), was used, and the mean score for each subscale was computed.…”
Section: 42mentioning
confidence: 99%
“…Thus, a large number of women are told during diagnostic testing that they do not, in fact, have breast cancer. There is robust evidence showing that, despite alleviation of the immediate threat of cancer, women who receive a benign diagnosis report persistent anxiety and other manifestations of psychological distress particularly intensely during the first 3-4 months after the diagnostic procedure [4][5][6][7][8][9][10][11][12][13] . In fact, recent research has shown that, compared with control subjects, these women report distress up to 8 months after the benign outcome 4 .…”
Section: Introductionmentioning
confidence: 99%